Rock your mocs - Goodluck, Laurel (Heartdrum, an imprint of HarperCollinsPublishers, 2023)
In this happy, vibrant tribute to Rock Your Mocs Day, observed yearly on November 15, author Laurel Goodluck (Mandan, Hidatsa, and Tsimshian) and artist Madelyn Goodnight (Chickasaw) celebrate the joy and power of wearing moccasins--and the Native pride that comes with them. A perfect book for Native American Heritage Month, and all year round!